Getting Real about Unknowns in Complex Policy Work - Andrews, Matt (Research on Improving Systems of Education (RISE), 2021)
As with all public policy work, education policies are demanding. Policy workers need to ‘know’ a lot—about the problems they are addressing, the people who need to be engaged, the promises they can make in response, the context they are working in, and the processes they will follow to implement. Most policy workers answer questions about such issues within the structures of plan and control processes used to devise budgets and projects. These structures limit their knowledge gathering, organization and sense-making activities to up-front planning activities, and even though sophisticated tools like Theories of Change suggest planners ‘know’ all that is needed for policy success, they often do not. Policies are often fraught with ‘unknowns’ that cannot be captured in passive planning processes and thus repeatedly undermine even the best laid plans. Through a novel strategy that asks how much one knows about the answers to 25 essential policy questions, and an application to recent education policy interventions in Mozambique, this paper shows that it is possible to get real about unknowns in policy work. Just recognizing these unknowns exist—and understanding why they do and what kind of challenge they pose to policy workers—can help promote a more modest and realistic approach to doing complex policy work.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); education / educação; government policy / politica governamental

Análise da Proposta do Orçamento do Estado 2021 - Mussagy, Ibraimo H. (Observatório do Meio Rural, 2021)
A actual Proposta do Orçamento do Estado (POE) 2021 é a segunda para o quinquénio 2020-2024 e foi elaborada num contexto de transformações económicas e sociais impostas por um novo “normal” provocado pela pandemia da COVID-19, que resultou na maior recessão mundial estimada em cerca de -4.9% para 2020. Essa recessão foi causada pelas medidas de contenção que resultaram na paralisação da actividade económica em grande parte das economias. Em linha com as actuais tendências da economia mundial, a economia Moçambicana também tem registado uma desaceleração (parágrafo 2 da POE 2021). Este texto tem a finalidade de analisar a POE 2021, tendo em conta este contexto. Para tal, a análise foi feita com base nos seguintes documentos: Plano Económico e Social (PES) 2021, POE 2021, mapas integrantes¹, leis orçamentais anteriores e os Relatórios de Execução Orçamental (REO) recentes. Faz-se a articulação destes documentos para se poder perceber a evolução das componentes da POE 2021. O texto compreende três secções, nomeadamente a introdução, a análise do orçamento, onde, de forma específica, o texto analisa os pressupostos macroeconómicos subjacentes à proposta, a evolução das receitas e das despesas, faz uma discussão sobre o défice orçamental, destaca os orçamentos sectoriais com enfase para agricultura, onde o projecto SUSTENTA prevalece em grande parte da discussão, aborda a questão da descentralização e discute o endividamento público, e, na última secção, apresenta-se o resumo das constatações.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; budget / orçamento; decentralization / descentralização; education / educação; health / saúde

O sector da educação em Moçambique: do acesso à qualidade epistémica do ensino primário - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Desde os primeiros anos de independência nacional, em 1975, o objectivo central da política educativa de Moçambique tem sido o de assegurar que todas as crianças em idade escolar tenham acesso à escola e nela permaneçam até concluírem a educação básica. Na prossecução deste objectivo, a expansão do acesso ao ensino primário foi realizada com relativo sucesso, uma vez que já se alcançou uma taxa líquida de cobertura escolar de quase 100%. Contudo, o impressionante aumento das taxas de escolarização não tem sido acompanhado por uma correspondente melhoria da qualidade da aprendizagem, havendo, em relação a este aspecto, sinais preocupantes de um retrocesso considerável. Partindo desta observação, o estudo identifica e analisa as variáveis do contexto institucional por detrás da 'escolarização sem aprendizagem'. Os resultados do estudo apontam para a (i) fraca capacidade do Estado, (ii) excessiva dependência da ajuda externa e (iii) fraco envolvimento e participação das comunidades na gestão das escolas, como sendo os factores de maior influência na fraca qualidade da aprendizagem no ensino primário.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The education sector in Mozambique: From access to epistemic quality in primary education - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Abstract: From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind ‘schooling without learning’. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude